2020
DOI: 10.1016/j.jad.2019.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported disability and quality of life in an online Australian community sample with suicidal thoughts

Abstract: Background: Limited research has been conducted to quantify the level of disability and health related quality of life (HRQoL) associated with suicidal thoughts and behaviour. The aims of the current study were to (1) describe levels of disability and HRQoL in an Australian sample of adults with suicidal ideation, (2) examine the effect of zero, one, or more than one previous suicide attempt on disability and HRQoL, and (3) describe the demographic and clinical characteristics associated with disability and HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
4
9
0
Order By: Relevance
“…Both undirected and directed analyses identified a connection between suicidal ideation and a reduced QOL and the most likely direction was from suicidal ideation to QOL, rather than vice versa. This was in line with other studies finding that suicidal ideation was associated with QOL (Almeida et al, 2021;Beşirli, Alptekin, Kaymak, & Özer, 2020;van Spijker et al, 2020) and suicidal thinking may reduce QOL (Hidalgo-Rasmussen & Martín, 2015;Kim et al, 2019;van Spijker, van Straten, Kerkhof, Hoeymans, & Smit, 2011). It should be noted that there are also some previous studies indicating that a low QOL could be a risk factor for suicidal ideation (Fairweather-Schmidt, Batterham, Butterworth, & Nada-Raja, 2016;Faure et al, 2018;Sinclair, Hawton, & Gray, 2010;van Spijker et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Both undirected and directed analyses identified a connection between suicidal ideation and a reduced QOL and the most likely direction was from suicidal ideation to QOL, rather than vice versa. This was in line with other studies finding that suicidal ideation was associated with QOL (Almeida et al, 2021;Beşirli, Alptekin, Kaymak, & Özer, 2020;van Spijker et al, 2020) and suicidal thinking may reduce QOL (Hidalgo-Rasmussen & Martín, 2015;Kim et al, 2019;van Spijker, van Straten, Kerkhof, Hoeymans, & Smit, 2011). It should be noted that there are also some previous studies indicating that a low QOL could be a risk factor for suicidal ideation (Fairweather-Schmidt, Batterham, Butterworth, & Nada-Raja, 2016;Faure et al, 2018;Sinclair, Hawton, & Gray, 2010;van Spijker et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The scores of HRQoL for the disabled on PCS, MCS, SF-6D and in each of the eight subscales of the SF-36 are smaller than those without disability. Similar associations between disability and HRQoL were reported in Australia [ 43 ] and North America [ 44 ]. One plausible reason for the association between disability and low HRQoL is the high perception of poor physical health due to the limitations in the performance of physical functions [ 43 ].…”
Section: Discussionsupporting
confidence: 81%
“…Similar associations between disability and HRQoL were reported in Australia [ 43 ] and North America [ 44 ]. One plausible reason for the association between disability and low HRQoL is the high perception of poor physical health due to the limitations in the performance of physical functions [ 43 ]. For example, an earlier study found that limitations in the performance of activities of daily living such as hygiene and dressing were major contributors to low HRQoL among persons with upper limb post-stroke spasticity [ 44 ].…”
Section: Discussionsupporting
confidence: 81%
“…Notably, functional impairment in this cohort was extremely elevated, such that the average score was more than double that of a normative sample of people with one or more mental disorders in the past 12 months highlighting the severity of this group (Andrews et al, 2009). Furthermore, because of the previously documented inverse relationship between suicidal ideation and perceived physical health (Dai et al, 2020; van Spijker et al, 2020), PRRCs should continue with a whole health approach through care coordination and treatment planning with primary care physicians, pain management specialists, holistic health providers, and other medical professionals. This incorporation of additional medical specialists (e.g., nurses) may also aid in improving overall well-being and functioning.…”
Section: Discussionmentioning
confidence: 99%